Spatio-Temporal Patterns of Intimate Partner Violence Victimization and Preventive Measures among Married Persons in Imo State, South East Nigeria - Iwuagwu, Tochi E; Kalu, Mgbo O; Ngwoke, Saint O. R; Yohanna, Wamanyi; Umar, Ibrahim; Iwuagwu, VivianMary A; Ejimonu, Ngozi C (Journal of Home Economics Research, 2024)
The study investigated spatio-temporal patterns of intimate partner violence (IPV) victimization and preventive measures among married persons in Imo State, Nigeria. It adopted cross-sectional research design. The population consisted of 1,649,032 married persons in the study area. The sample size was 1,488 married persons drawn using multi-stage sampling procedure and purposive sampling technique. Questionnaire was used for data collection. Frequency, percentage, and binary logistic regression were used for data analyses. Findings reveal that married persons mostly experienced intimate partner violence in the home (23.4%), followed by public places (17.9%), and workplaces (15.4%). overall, married persons mostly experienced intimate partner violence in the morning (19.1%), followed by evening/night (14.9%), and afternoon (12.3%). Married persons indicated that all the proposed preventive measures for IPV were appropriate Gender, education level, place of residence, and length of marriage (p≤.05) were significantly associated with the patterns of various forms of intimate partner violence among married persons.